2004
DOI: 10.1182/blood-2004-05-2008
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of hemophilia treatment in the Netherlands, 1972-2001

Abstract: Since the introduction of replacement therapy in the early 1960s by the infusion of plasma-derived factor VIII and IX preparations, important changes have occurred for hemophilia patients. We studied the medical and social developments over 30 years of hemophilia treatment. Since 1972, 5 cross-sectional national postal surveys among all hemophilia patients in the Netherlands were performed, the latest in 2001. The prestructured questionnaires included items on treatment, the presence of inhibitory antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(150 citation statements)
references
References 26 publications
9
136
5
Order By: Relevance
“…Since then nationwide surveys were repeated in 1978,1985,1992 and in 2001 [21][22][23][24]. These studies aimed at assessing the medical and social consequences of haemophilia in the Netherlands.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then nationwide surveys were repeated in 1978,1985,1992 and in 2001 [21][22][23][24]. These studies aimed at assessing the medical and social consequences of haemophilia in the Netherlands.…”
Section: Settingmentioning
confidence: 99%
“…The mean age of patients differed according to severity of haemophilia and HCV status; patients with severe haemophilia, who were never infected, were younger [mean age 23 years, 95% confidence interval (CI) [19][20][21][22][23][24][25][26][27][28] …”
Section: Hepatitis Cmentioning
confidence: 99%
“…This is considered the gold standard of preventive care and is implemented in many Scandinavian and Northern European countries. 21,22 Although the World Health Organization, the National Hemophilia Foundation, and the World Federation of Hemophilia recommend FVIII prophylaxis as the main approach for treating children, 20 in several countries patients are treated with an on-demand regimen, that is, FVIII infusions given only when bleeding occurs.…”
Section: Hemophilia and Factor VIII Treatment Strategiesmentioning
confidence: 99%
“…Hemarthrosis as the predominant presentation with most affected joint being knee joints were also found in Korean study 21 . However many other studies conducted in Netherlands, France and Spain showed ankle joint as mostly affected joints 22,23,24 .…”
Section: Clinical Manifestationmentioning
confidence: 99%